Therapeutic Agreement Between Doctor and Patient: Juridical Analysis in Civil Law - Aisyah, Aisyah; Prananda, Arya Tjipta; Dasatjipta, Guslihan; Afrita, Afrita (Ipso Jure, 2025)
The relationship between doctor and patient is not only ethical and professional, but also has a strong legal dimension, particularly in the form of therapeutic agreements. This agreement forms the basis for initiating medical proceedings and creates a binding legal relationship based on the principles of civil law. This study aims to analyze juridically the existence and validity of therapeutic agreements within the framework of civil law, examine the forms of legal liability arising from violations, and evaluate evidentiary instruments in medical disputes. The method used is normative legal research with a legislative approach, supported by an analysis of legal literature and jurisprudence studies. The results of the study show that although therapeutic agreements are often not stated in writing, their existence is still valid and binding if they meet the legal requirements of the agreement as stipulated in Article 1320 of the Civil Code. Informed consent serves as proof of the implementation of the agreement and as the basis for legal defense in disputes. Civil liability can be imposed both on doctors personally and hospitals as institutions through the doctrine of vicarious liability, and forms of compensation include material and immaterial losses. Dispute resolution through non-litigation channels such as mediation and the role of the Indonesian Medical Discipline Honorary Council (MKDKI) also have an important contribution in maintaining a balance between patient protection and medical professional accountability.